Enhancing Non-Medical Patient Experience Through Omnichannel Service Design in a Digitalizing Hospital Contact Center - Elza Zuriawan; Catur Widayati (Journal of Sustainable Economic and Business, 2026)
Objectives: This research explores the non-clinical customer experience (CX) within the contact center of a premium private hospital. It aims to design a model for enhancement by leveraging service design and digital integration to minimize inconsistencies across different communication channels.Methodology: Utilizing a qualitative, interpretivist methodology, the study involved observing contact center processes and conducting semi-structured interviews with internal stakeholders and patients. Thematic analysis was employed to uncover patterns in experiences, pinpoint key obstacles, and identify areas for enhancement.Finding: The study found that patient experiences were negatively impacted by long wait times, unanswered calls, and disjointed digital communication platforms. Trust and perceptions of professionalism were strongly influenced by the responsiveness and empathy demonstrated by contact center agents. The research introduces an integrated “one-door” omnichannel approach, utilizing tools such as customer journey mapping and service blueprinting, and recommends solutions like call-back services and instant messaging chatbots.Conclusion: By aligning human-centered service design with an omnichannel framework, healthcare providers can foster a more cohesive and sustainable non-clinical CX. This integration helps reduce service fragmentation, ensures consistent responses, and strengthens the contact center’s role as a pivotal patient engagement point.